ABCB4 disease: Many faces of one gene deficiency - Sticova, Eva; Jirsa, Milan (Annals of hepatology, 2020)
ATP-binding cassette (ABC) subfamily B member 4 (ABCB4), also known as multidrug resistance protein 3 (MDR3), encoded by ABCB4, is involved in biliary phospholipid secretion, protecting hepatobiliary system from deleterious detergent and lithogenic properties of the bile. ABCB4 mutations altering canalicular ABCB4 protein function and expression may have variable clinical presentation and predispose to several human liver diseases. Well-established phenotypes of ABCB4 deficit are: progressive familial intrahepatic cholestasis type 3, gallbladder disease 1 (syn. low phospholipid associated cholelithiasis syndrome), high ɣ-glutamyl transferase intrahepatic cholestasis of pregnancy, chronic cholangiopathy, and adult biliary fibrosis/cirrhosis. Moreover, ABCB4 aberrations may be involved in some cases of drug induced cholestasis, transient neonatal cholestasis, and parenteral nutrition-associated liver disease. Recently, genome-wide association studies have documented occurrence of malignant tumours, predominantly hepatobiliary malignancies, in patients with ABCB4/MDR3 deficit. The patient's age at the time of the first presentation of cholestatic disease, as well as the severity of liver disorder and response to treatment are related to the ABCB4 allelic status. Mutational analysis of ABCB4 in patients and their families should be considered in all individuals with cholestasis of unknown aetiology, regardless of age and/or time of onset of the first symptoms.
Keywords: nemoci žlučníku; P-glykoproteiny; Bile Duct Diseases; Liver Diseases; Ursodeoxycholic Acid; Chemical and Drug Induced Liver Injury; Cholestasis; Cholagogues and Choleretics; Parenteral Nutrition; alely; parenterální výživa; cholelitiáza; lidé; Cholestasis, Intrahepatic; komplikace těhotenství; biliární cirhóza; Gallbladder Diseases; Liver Cirrhosis, Biliary; nemoci jater; cholestáza; Pregnancy Complications; nemoci žlučových cest; ATP Binding Cassette Transporter, Subfamily B; cholagoga a choleretika; věk při počátku nemoci; lékové postižení jater; Age of Onset; kyselina ursodeoxycholová; Alleles; Humans; Cholelithiasis; intrahepatální cholestáza